Research on Measurement Traceability Method of Dynamic Shear Rheometer. Issue 4 (March 2021) - Miao, Na; Peng, Lu; Chen, Lei; You, Chunmei; Wang, Yixu
Abstract: The dynamic shear rheometer is the basic instrument for studying viscoelastic materials. In this paper, the influences of the accuracy of dynamic shear rheometer were analyzed, calibration parameters were proposed and verified through experiments, and the extended uncertainty was 3.0 (k=2), which verified the feasibility of using viscosity reference materials as a technology to realize the measurement traceability of dynamic shear rheometer, and the traceability method can be promoted and applied to the traceability of various equipment.